2020
DOI: 10.1186/s12889-020-08986-x
|View full text |Cite
|
Sign up to set email alerts
|

“Death is a better option than being treated like this”: a prevalence survey and qualitative study of depression among multi-drug resistant tuberculosis in-patients

Abstract: Background: Understanding of the relationship between multi-drug resistant tuberculosis and mental health is limited. With growing prevalence of multi-drug resistant tuberculosis, addressing mental ill-health has potential to improve treatment outcomes and well-being. In several low and middle-income contexts hospitalisation during treatment is common. Understanding of the impact on mental ill-health are required to inform interventions for patients with multi-drug resistant tuberculosis. Our aim was to identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
(44 reference statements)
1
19
0
Order By: Relevance
“…Otherwise, in DR-TB therapy, the existing therapeutics regimen was shown to be extremely burdensome for most patients owing to ADR. 36 , 39 , 45 Some studies reported that ADR more likely reduced HR-QoL. 20 , 22 ADR is included in the burden of medicine, a term that refers to workloads that are withstood by a person who undergoes therapy and can affect their QoL, especially in a long-term therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Otherwise, in DR-TB therapy, the existing therapeutics regimen was shown to be extremely burdensome for most patients owing to ADR. 36 , 39 , 45 Some studies reported that ADR more likely reduced HR-QoL. 20 , 22 ADR is included in the burden of medicine, a term that refers to workloads that are withstood by a person who undergoes therapy and can affect their QoL, especially in a long-term therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data indicated that the majority of patients feel depressed owing to side effects. 45 Another study revealed that the side effects were the most significant factors of depression among MDR-TB patients (aOR 20.7, 95% CI 1.2–355.7). 44 Patients were often depressed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations